The Effect Of Tradition And Nostalgia On Regional Ethnocentrism And Edible Product Buying - Shanmugam, A.R. Harihara; Ramakrishnan, Dr.P.R. (The journal of contemporary issues in business and government, 2021)
The study as highlighted in the literature, edible product produced in a traditional manner are getting concentration in recent scenario. The reason for people concentrated in this products health concerns is one of the reason, they wish to give preference to regional products at the same time. The present study aims to investigate the regional ethnocentrism and cold press oil buying relationship, at the same time the study also investigate the indirect relationship through tradition and nostalgia. The study consist of 158 consumers as a respondents. The women respondents are majority in this research. The ages of those surveyed were below 30 years to above 50 years. To assess regional ethnocentrism, six indicators and to assess tradition and nostalgia eight indicators have been used.Cold-press oil buying frequency is assess by respondents were asked to think and specify on purchased Cold-press oil in the earlier months. And the Cold-press oil buying Willingness is assess by think and specify the likelihood to buy Cold-press oil. The study reveals that the regional ethnocentrism directly influence the cold press oil buying, and also indirectly through tradition and nostalgia.